2018
DOI: 10.3389/fmicb.2018.01415
|View full text |Cite
|
Sign up to set email alerts
|

Endosymbionts Alter Larva-to-Nymph Transstadial Transmission of Babesia microti in Rhipicephalus haemaphysaloides Ticks

Abstract: Maternally inherited endosymbionts inhabit a variety of arthropods. Some of them can protect the arthropod host against a wide range of pathogens. However, very little is known about the association between endosymbionts and pathogen susceptibility in ticks. The present study investigated the effect of endosymbionts on larva-to-nymph transstadial transmission of Babesia microti by Rhipicephalus haemaphysaloides ticks. Engorged female ticks were injected with PBS, ciprofloxacin or kanamycin. The offspring larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…A reduced infection rate of R. haemaphysaloides with CLE correlated with a lower rate of transstadial transmission of Babesia microti. Candidatus Midichloria mitochondrii , another tick endosymbiont, is known to influence the occurrence and ability to detect tick-borne pathogens in I. ricinus ( 159 , 160 ).…”
Section: Discussionmentioning
confidence: 99%
“…A reduced infection rate of R. haemaphysaloides with CLE correlated with a lower rate of transstadial transmission of Babesia microti. Candidatus Midichloria mitochondrii , another tick endosymbiont, is known to influence the occurrence and ability to detect tick-borne pathogens in I. ricinus ( 159 , 160 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Coxiella in ticks includes both symbiotic and pathogenic bacteria (Nardi et al, 2021), and non-pathogenic symbionts may be important in the transmission of TBPs (Bonnet et al, 2017). Li et al (2018) suggested that Coxiella was likely an important defensive endosymbiont, and TBPs prevalence was decreased, with this being dependent on reduced Coxiella endosymbiont in ticks. We showed that the Coxiella abundance was decreased and B. microti infection increased in AT adults compared to the CT adults, which is consistent with the results of Li et al However, TBPs transmission needs further study and may lead to a potential biological strategy for TBPs control.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Coxiella in ticks includes both symbiotic and pathogenic bacteria ( Nardi et al., 2021 ), and non-pathogenic symbionts may be important in the transmission of TBPs ( Bonnet et al., 2017 ). Li et al. (2018) suggested that Coxiella was likely an important defensive endosymbiont, and TBPs prevalence was decreased, with this being dependent on reduced Coxiella endosymbiont in ticks.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have investigated whether dysbiosing ticks influences their susceptibility to acquiring tick-borne pathogens [8, 11-13]. In some systems, microbiome disruption makes tick species more susceptible to infection with tick-borne pathogens [8, 13], whereas other systems found the opposite effect [11, 12]. In the present study, we found no evidence that microbiome disruption influenced B. afzelii infection rates or the B. afzelii spirochete load in infected ticks.…”
Section: Discussionmentioning
confidence: 99%
“…For successful transmission, however, vector-borne pathogens must contend with both the immunological defenses of the arthropod vector, and the community of other microbiota that inhabit it [4-7], and it is now clear that endogenous microbes can shape the competence of diverse arthropod vectors in acquiring and transmitting pathogens [8-12]. Experimental perturbations of the microbiome (‘dysbiosis’) via the use of antibiotics or other methods have, in various contexts, been shown to either increase or decrease the susceptibility of arthropods to colonization by vector-borne pathogens [8, 10, 12, 13]. In particular, the introduction of the intracellular bacterium Wolbachia into mosquito vectors [14] can dramatically reduce mosquito competence to vector arboviruses, malaria parasites, and filarial nematodes (Kambris et al 2009, Moreira et al 2009, Bian et al 2010).…”
Section: Introductionmentioning
confidence: 99%